1946
DOI: 10.1021/ie50440a023
|View full text |Cite
|
Sign up to set email alerts
|

Styrene Production by Catalytic Dehydrogenation

Abstract: Laboratory data are presented on the catalytic dehydrogenation of ethylbenzene over a chromia-alumina catalyst in the presence of benzene. Reduction of the partial pressure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1951
1951
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The ultimate yield for a given conversion has increased by about 5%. Mavity et al (16,17) obt a i n e d t h e s a m e type of curves in the dehydrogenation of ethylbenzene using benzene as a diluent.…”
Section: Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate yield for a given conversion has increased by about 5%. Mavity et al (16,17) obt a i n e d t h e s a m e type of curves in the dehydrogenation of ethylbenzene using benzene as a diluent.…”
Section: Effectmentioning
confidence: 99%
“…The diluted feed produced considerably more gas. Mavity et al (16,17) showed that at 1112°F. (600°C.)…”
Section: Effect Of Process Variablesmentioning
confidence: 99%
“…2). Likewise the corresponding alkyenes substrates can be readily accessed at industrial scale from simple dehydrogenation of the corresponding styrene or alkane precursors [23][24][25][26][27][28][29][30] which although currently are most often sourced from petrochemical feedstock are increasingly being derived from bio-feeds. [31][32][33] Such consideration gives additional merit to a future production route originating from these starting materials.…”
Section: Introductionmentioning
confidence: 99%